Understanding children's informal learning : appreciating everyday learners - Bourke, Roseanna; O'Neill, John; Loveridge, Judith (Emerald studies in out-of-school learning, 2024)
Learning and personal development are integral to being a person, and learning and teaching are integral to life as a social being. Understanding Children's Informal Learning presents children's informal learning out-of-school and explores how this knowledge can enhance teaching and learning practice in the classroom. The authors focus on the richness of children's everyday learning, and in what ways children, teachers and schools can work to bring more of the everyday learning strengths that all children have into the interactional framework of the classroom. Offering practical applications for teachers and other education professionals, the chapters work to ensure children's voices are heard and actively influence understandings of learning, so that out-of-school learning is legitimised as a critical constituent of in-school learning. Addressing the need to provide a strong 'student voice' component and strategies to support children's learning both in-school and out-of-school, Understanding Children's Informal Learning furthers comprehensive education research, policy, and practice.